Karakteristik Sifat Fisikokimia Pati Gembili (Dioscorea esculenta L.) dengan Modifikasi Annealing - Jambormias, Karlos L; Polnaya, Febby J; Ega, La (Universitas Pattimura, 2024)
The objective of this study was to examine the physical properties of gembili starch from local area, taking into type of gembili and the duration of annealing time treatments. A factorial randomized design was employed, consisting of two factors - the type of gembili (ordinary and kapok) and the duration of annealing time (0, 12, 16, and 20 hours) with three replications. This resulted in eight treatment combinations, and various parameters were analyzed, including water content, ash content, swelling power, water absorption, pH, and amylose content. The results of the physical property analysis revealed that annealing-modified gembili starch had a moisture content ranging from 10.25% to 13.48%, ash content ranging from 0.11% to 0.36%, swelling power ranging from 19.25 to 33.41 g/g, water absorption ranging from 15.3% to 20.9%, pH ranging from 6.2 to 6.5, and amylose content ranging from 20.89% to 26.2%. Overall, this study provides valuable insights into the physical properties of gembili starch in relation to the type of gembili treatment and the duration of annealing time.